2014
DOI: 10.1021/jm500335h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Daclatasvir, a Pan-Genotypic Hepatitis C Virus NS5A Replication Complex Inhibitor with Potent Clinical Effect

Abstract: The discovery and development of the first-in-class hepatitis C virus (HCV) NS5A replication complex inhibitor daclatasvir (6) provides a compelling example of the power of phenotypic screening to identify leads engaging novel targets in mechanistically unique ways. HCV NS5A replication complex inhibitors are pan-genotypic in spectrum, and this mechanistic class provides the most potent HCV inhibitors in vitro that have been described to date. Clinical trials with 6 demonstrated a potent effect on reducing pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 116 publications
0
59
0
Order By: Relevance
“…The non-nucleoside polymerase inhibitor sofosbuvir (SOF) was launched in several countries at the beginning of 2014, followed by SMV, an NS3 protease inhibitor, and DCV, an NS5A replication complex inhibitor. Recent studies have shown that SMV, when combined with PegIFN and RBV, results in markedly better SVR rates than PegIFN and RBV alone for patients with HCV GT1 [16,17,18]. In addition, one study has demonstrated the potent pan-genotypic antiviral effectiveness of an IFN-sparing treatment regimen using DCV [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-nucleoside polymerase inhibitor sofosbuvir (SOF) was launched in several countries at the beginning of 2014, followed by SMV, an NS3 protease inhibitor, and DCV, an NS5A replication complex inhibitor. Recent studies have shown that SMV, when combined with PegIFN and RBV, results in markedly better SVR rates than PegIFN and RBV alone for patients with HCV GT1 [16,17,18]. In addition, one study has demonstrated the potent pan-genotypic antiviral effectiveness of an IFN-sparing treatment regimen using DCV [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SMV, when combined with PegIFN and RBV, results in markedly better SVR rates than PegIFN and RBV alone for patients with HCV GT1 [16,17,18]. In addition, one study has demonstrated the potent pan-genotypic antiviral effectiveness of an IFN-sparing treatment regimen using DCV [18]. Moreover, treatment for 24 weeks with SFV plus DCV or SMV with or without RBV has been shown to be highly effective for HCV GT1 patients [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent success stories around hepatitis C virus (HCV) inhibitors [3], cystic fibrosis 'correctors' [4] and RNA splicing modulators for spinal muscular atrophy [5,6] are all from this category. For mechanisms for which we have a high degree of confidence, for example a Mendelian disorder and a molecule that can modulate the disease phenotype in a cellular model, we might be comfortable to progress the program by skipping a few steps in the typical workflow or without knowing the molecular mechanism of action or even the target of the molecule.…”
Section: Translatability In Phenotypic Drug Discoverymentioning
confidence: 99%
“…7 To date, four NS5A inhibitors have gained regulatory approval and are shown in Figure 1. [8][9][10][11] A matched and mixed capping SAR study was conducted on the tetracyclic indole class of HCV NS5A inhibitors to examine the influence of modifications of this region on the overall HCV virologic resistance profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Approved HCV NS5A inhibitors. [8][9][10][11] In a continued effort to explore the tetracyclic indole class of NS5A inhibitors, efforts were undertaken to examine the impact of structural modifications of the two imidazole L-Pro-L-Val methyl carbamate (Moc) regions (Figure 1). While a brief SAR exploration had been previously conducted in an earlier series (MK-4882) to replace the two terminal L-valine methyl carbamate moieties (Val Moc), 11 we sought to explore the impact on the virologic profile of broader changes to the amino acid end caps in the current series.…”
Section: Introductionmentioning
confidence: 99%